Sustainability Accounting: A Perspective of Symbolic Interactionism - Yohanes Fabiyola Halan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the understanding and interpretation of the concept of sustainability in accounting based on existing literature. Utilizing an interpretive qualitative approach, this research examines various scholarly articles and publications related to sustainability accounting to explore how the meaning of sustainability is shaped through social interactions among stakeholders. The analysis results indicate that sustainability accounting is not only related to measuring environmental and social performance but is also influenced by the social and cultural contexts that shape perceptions and practices of accounting. These findings underscore the importance of understanding sustainability accounting as a dynamic and contextual process, highlighting the need for a more holistic approach in comprehending sustainability indicators. Practically, this study highlights the importance of transparency, stakeholder engagement, and collaborative dialogue to build more effective social and environmental accountability. By understanding the social processes underlying the construction of sustainability meanings, organizations can strengthen the credibility of their sustainability reports, reduce the risks of information manipulation, and integrate sustainability values into their business strategies more meaningfully. This research contributes to the accounting literature by providing new insights into how symbolic interactionism theory can be applied in the analysis of sustainability accounting practices.